Praktik Upah Panjar Molang Sapi Prespektif Hukum Islam di Desa Bongsopotro Kecamatan Saradan Kabupaten Madiun - Thorikul Janah; Mohammad Hipni (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
The aim of this research is to find out how the cow molang down payment is used in Bongsopotro Village, Saradan District, Madiun Regency from the perspective of Islamic law. The research approach used is qualitative descriptive field research (field study). normative method, which includes the application of Islamic law to solve problems. The results of the research show that the implementation of buying and selling cattle with molang/intermediaries from other people who are experts in their field is a customary tradition for some people in Bongsopotro village. The payment transaction process for purchasing cattle is payment by down payment or by way of down payment from the total price, up to a number of market days for legi and wages and then paying off the entire money. from Bongsopotro village. In Islamic law, down payment is an order contract (istisna') so it is valid according to Islamic law.